Composite tool coating and preparation method thereof
By covering the molybdenum disulfide interface layer on the tool surface, the problem of low bonding strength between the AlCrN hard coating and metal is solved, and a higher bonding strength and service life are achieved.
Patent Information
- Application Number
- CN202011377458.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-11-30
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2040-11-30
AI Technical Summary
The bonding strength between the AlCrN hard coating of existing tools and the metal is low, resulting in the coating being easily shedded under the action of external forces.
A layer of interface layer with molybdenum disulfide as the main body is coated between the hard coating and the tool surface. The bonding strength between the tool surface and the coating is improved through sol deposition technology, and the high load-bearing performance of molybdenum disulfide is reduced under the influence of stress concentration under external forces.
The bonding strength between the AlCrN tool coating and the tool surface is significantly improved, the peeling phenomenon of the hard coating is reduced, and the bearing performance and service life of the coating are improved.
Smart Images

Figure CN112663060B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of hard coatings, and more specifically, relates to a composite tool coating and a preparation method thereof. Background Art
[0002] With the development of manufacturing industry, hard coating has entered a new stage of multi-element and multi-layer coating from the initial simple binary coating. The technical solution of Cr-AlN coating formed by adding Al element to CrN coating has obvious improvements in hardness, high temperature resistance and wear resistance. With the increase of Al element content, the performance of AlCrN coating formed when the Al atomic content exceeds 50% is further improved, which greatly expands the application field of ternary coating and is expected to become the most typical representative of current ternary nitride coating.
[0003] Since the AlCrN hard coating of the existing tools and the tool surface are directly loaded by deposition, in actual use, when the metal and the coating are subjected to external force, due to the poor bearing performance of the coating, the bonding strength between the hard coating and the metal is low under the action of external force, which will cause the hard coating to easily fall off during actual use. Summary of the invention
[0004] The present invention aims to solve at least one of the technical problems existing in the prior art.
[0005] In view of this, the present invention provides a composite tool coating, which has high bonding strength between the composite tool coating and the substrate, excellent coating load-bearing performance, and high bonding strength between the hard coating and the metal under the action of external force.
[0006] The invention also provides a method for preparing a composite tool coating, which has simple preparation steps and improves preparation efficiency.
[0007] According to the preparation method of the copper-based powder metallurgy friction material of the embodiment of the present invention, it includes an interface layer, a CrN bonding layer and an AlCrN coating layer coated in sequence from the inside to the outside, wherein the interface layer is a matrix gel liquid prepared by mixing nano-molybdenum disulfide and citric acid solution, which is prepared by drying and coating.
[0008] According to the composite tool coating of the embodiment of the present invention, an interface layer mainly composed of molybdenum disulfide is coated between the hard coating and the tool surface to improve the bonding performance between the tool surface and the deposited hard coating. Since molybdenum disulfide is deposited on the material surface through a sol deposition scheme, on the one hand, the bonding strength between the sol material and the tool material surface is relatively high, which can significantly improve the bonding strength between the tool surface and the coating. On the other hand, when the hard coating is subjected to external force, since molybdenum disulfide has good high load-bearing performance, the stress unloading effect of the high load-bearing performance of molybdenum disulfide can reduce the coating damage caused by stress concentration generated under the action of external force, thereby effectively improving the bonding strength between the AlCrN tool coating and the tool surface and reducing the shedding phenomenon of the AlCrN hard coating.
[0009] The composite tool coating according to the embodiment of the present invention may also have the following additional technical features:
[0010] According to one embodiment of the present invention, the interface layer also includes a metal complex sol solution, and the preparation steps of the metal complex sol solution are: (1) adding polyvinyl alcohol to dimethyl sulfoxide, stirring and mixing, and collecting the mixed solution; (2) taking the mixed solution, the metal complex and sodium bisulfate, stirring and mixing, heating and heat preservation reaction treatment under a nitrogen atmosphere to obtain a mixed solution; (3) adding the mixed solution to acetone, stirring and mixing, standing and aging, filtering and collecting the precipitate, and adding the precipitate to the metal ion solution to obtain a metal complex sol solution.
[0011] According to an embodiment of the present invention, the metal ion solution includes any one of a ferric chloride solution, a zinc chloride solution or an aluminum chloride solution.
[0012] According to one embodiment of the present invention, the metal complex is 3,4-dihydroxyphenylalanine.
[0013] The preparation method of the composite tool coating according to the second embodiment of the present invention includes: S1, taking a tool, grinding and washing it, and letting it stand to dry to obtain a surface-treated tool; S2, stirring and mixing the metal complex sol solution and the matrix gel solution and dispersing them, collecting the modified dispersed gel solution and applying it to the surface of the surface-treated tool, heating and calcining after drying, and letting it stand to cool to room temperature to obtain an interface layer; S3, after the interface layer is coated, the tool coated with the interface layer is placed on a rotating rack, and Cr is used as a target material to deposit a CrN bonding layer; S4, after the CrN bonding layer is deposited, AlCr is used as a target material to deposit an AlCrN coating layer, and a composite tool coating can be prepared.
[0014] According to an embodiment of the present invention, the grinding process described in step S1 is performed by using 800#, 1200# and 1500# sandpaper respectively.
[0015] According to one embodiment of the present invention, the heating and heat preservation calcination step described in step S2 is: heating to 150-180°C at 3°C / min, heat preservation treatment for 3-5h, and then heating to 300-350°C at 1°C / min and heat preservation heating.
[0016] According to an embodiment of the present invention, the CrN bonding layer deposited in step S3 has a thickness of 0.05-0.10 μm and a deposition temperature of 480-550° C.
[0017] According to one embodiment of the present invention, the AlCrN coating layer in step S4 has a deposition thickness of 3-5 μm and a deposition temperature of 480-500° C.
[0018] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0020] Figure 1 The figure is a flow chart of a method for preparing a composite tool coating according to an embodiment of the present invention. DETAILED DESCRIPTION
[0021] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present invention, and cannot be understood as limiting the present invention.
[0022] The preparation method of the copper-based powder metallurgy friction material according to an embodiment of the present invention is described in detail below with reference to the accompanying drawings.
[0023] Firstly, the composite tool coating according to the embodiment of the present invention comprises: an interface layer, a CrN bonding layer and an AlCrN coating layer coated sequentially from the inside to the outside, wherein the interface layer is a matrix gel liquid prepared by mixing nano-molybdenum disulfide and citric acid solution, which is prepared by drying and coating.
[0024] Therefore, the present application coats an interface layer mainly composed of molybdenum disulfide between the hard coating and the tool surface to improve the bonding performance between the tool surface and the deposited hard coating. Since molybdenum disulfide is deposited on the material surface through a sol deposition scheme, on the one hand, the bonding strength between the sol material and the tool material surface is relatively high, which can significantly improve the bonding strength between the tool surface and the coating. On the other hand, when the hard coating is subjected to external force, since molybdenum disulfide has good high load-bearing performance, the stress concentration generated under the action of external force can reduce the stress unloading effect of molybdenum disulfide. The stress concentration can reduce the phenomenon of coating damage. The bonding strength between the AlCrN tool coating and the tool surface is effectively improved, and the shedding phenomenon of the AlCrN hard coating is reduced.
[0025] According to one embodiment of the present invention, the interface layer also includes a metal complex sol solution, and the preparation steps of the metal complex sol solution are: (1) adding polyvinyl alcohol to dimethyl sulfoxide, stirring and mixing, and collecting the mixed solution; (2) taking the mixed solution, the metal complex and sodium bisulfate, stirring and mixing, heating and heat preservation reaction treatment under a nitrogen atmosphere to obtain a mixed solution; (3) adding the mixed solution to acetone, stirring and mixing, standing and aging, filtering and collecting the precipitate, and adding the precipitate to the metal ion solution to obtain a metal complex sol solution.
[0026] By adopting the above technical scheme, the metal complex sol solution is modified and added, which can effectively improve the bonding performance between the metal material and the gel material. On this basis, the highly bonded metal complex sol can effectively improve the bonding strength between the interface layer and the tool surface, thereby improving the bonding strength between the AlCrN tool coating and the tool surface and reducing the shedding phenomenon of the AlCrN hard coating.
[0027] In some specific embodiments of the present invention, the metal ion solution includes any one of ferric chloride solution, zinc chloride solution or aluminum chloride solution.
[0028] Therefore, by using metal ion solution as the added modifying material, good sol properties can be effectively formed between the metal ion solution and the metal complex. The sol material prepared in this way can effectively improve the density of the interface layer, thereby effectively improving the density performance of the interface layer, so that the interface layer can withstand stronger external pressure, thereby reducing the shedding phenomenon of the AlCrN hard coating.
[0029] Furthermore, the metal complex is 3,4-dihydroxyphenylalanine.
[0030] By adopting the above technical scheme, since the present application adopts 3,4-dihydroxyphenylalanine for modification, the material has the ability of rapid adhesion and chemical cross-linking curing. After it is added to the inside of the sol, it can be effectively adhered to the surface of the tool material. At the same time, since 3,4-dihydroxyphenylalanine also has a good complexing ability with metal ions, the density performance of the interface layer is effectively improved, and the shedding phenomenon of the AlCrN hard coating is improved.
[0031] In the second aspect, the present application provides a method for preparing a composite tool coating, which comprises: S1, taking a tool, grinding and washing it, and letting it stand to dry to obtain a surface-treated tool; S2, stirring and mixing the metal complex sol solution and the matrix gel solution, and dispersing them, collecting the modified dispersed gel solution and applying it to the surface of the surface-treated tool, heating and calcining after drying, and letting it stand to cool to room temperature to obtain an interface layer; S3, after the interface layer is coated, the tool coated with the interface layer is placed on a rotating rack, and Cr is used as a target material to deposit a CrN bonding layer; S4, after the CrN bonding layer is deposited, AlCr is used as a target material to deposit an AlCrN coating layer, and a composite tool coating can be prepared.
[0032] Therefore, the present application adopts the addition of Al element, which can refine the coating grains, cause nitride lattice distortion to form a strengthening effect, and at high temperatures, can form dense Al and Cr oxides, which have the function of protecting the internal coating. On this basis, the interface layer set between the tool surface and the deposited coating is molybdenum disulfide. Due to its excellent structural properties, when the hard coating is subjected to external force, the stress intensity of the part where the external force acts is effectively reduced, thereby reducing the phenomenon of stress concentration at the action site causing damage to the hard coating.
[0033] Optionally, the grinding process described in step S1 is performed by using 800#, 1200# and 1500# sandpaper respectively.
[0034] The present application uses sandpaper of various specifications for grinding, which can thoroughly treat the oxide layer on the surface of the tool, so that in the subsequent coating process, the tool surface and the interface layer can form direct contact and good bonding performance.
[0035] In some specific embodiments of the present invention, the heating and heat preservation calcination step described in step S2 is: heating to 150-180°C at 3°C / min, heat preservation for 3-5h, and then heating to 300-350°C at 1°C / min and heat preservation.
[0036] The present application adopts a programmed temperature increase and heating calcination scheme to coat an interface layer on the surface of the tool. The overall scheme is simple and easy to implement, with low cost and simple operation steps. While effectively reducing the preparation cost, the high-temperature calcination treatment can effectively form a good coating load between the interface layer and the tool surface, thereby improving the bonding performance between the subsequent coating and the tool surface.
[0037] In some specific embodiments of the present invention, the CrN bonding layer deposited in step S3 has a thickness of 0.05-0.10 μm and a deposition temperature of 480-550° C.
[0038] By adopting the above technical scheme, the thickness of the CrN bonding layer is optimized. Since CrN has high hardness, low friction coefficient and small difference in physical and mechanical performance parameters with cemented carbide, it is used as a bonding layer with lower thickness and its thickness size is optimized. This can effectively reduce the structural effect of the overall coating caused by excessive thickness of the bonding layer. Therefore, the optimized CrN bonding layer can not only effectively improve the structural properties of the hard coating material, but also effectively reflect the effects of its high hardness and low friction coefficient, further improving the mechanical strength and mechanical properties of the coating after combination with the tool surface.
[0039] According to one embodiment of the present invention, the AlCrN coating layer in step S4 has a deposition thickness of 3-5 μm and a deposition temperature of 480-500° C.
[0040] By adopting the above technical solution, the AlCrN coating layer is set as the outermost structure of the hard coating. Since Al element is added to the coating, the addition of Al element can refine the coating grains and cause nitride lattice distortion to form a strengthening effect. It can also form dense Al and Cr oxides at high temperatures, which have the function of protecting the internal coating, thereby effectively improving the strength of the hard coating and making it have excellent hardness performance. Therefore, during use, it can produce a good impact resistance effect against the collision of high hardness materials.
[0041] In summary, the present application coats an interface layer composed mainly of molybdenum disulfide between the hard coating and the tool surface to improve the bonding performance between the tool surface and the deposited hard coating. Since molybdenum disulfide is deposited on the material surface through a sol deposition scheme, on the one hand, the bonding strength between the sol material and the tool material surface is relatively high, which can significantly improve the bonding strength between the tool surface and the coating. On the other hand, when the hard coating is subjected to external force, since molybdenum disulfide has good high load-bearing performance, the stress concentration generated under the action of external force can reduce the stress unloading effect of molybdenum disulfide, which causes damage to the coating. This effectively improves the bonding strength between the AlCrN tool coating and the tool surface and reduces the shedding phenomenon of the AlCrN hard coating.
[0042] By using metal ion solution as the added modified material, good sol properties can be effectively formed between the metal ion solution and the metal complex. The sol material prepared in this way can effectively improve the density of the interface layer, thereby effectively improving the density performance of the interface layer, so that the interface layer can withstand stronger external pressure, thereby reducing the shedding phenomenon of the AlCrN hard coating.
[0043] By adding Al element to the coating layer, the addition of Al element can refine the coating grains and cause nitride lattice distortion, forming a strengthening effect, and can form dense Al and Cr oxides at high temperatures, which have the function of protecting the internal coating, thereby effectively improving the strength of the hard coating and making it have excellent hardness performance, so that during use, it can produce good impact resistance to the collision of high hardness materials.
[0044] The composite tool coating and the preparation method thereof according to the embodiment of the present invention are described in detail below in conjunction with specific embodiments.
[0045] Example 1
[0046] Polyvinyl alcohol was added to dimethyl sulfoxide at a mass ratio of 1:25, the mixture was stirred and mixed, and the mixture was collected. The mixture was then added to a three-necked flask, stirred and mixed, and 45 parts of the mixture, 3 parts of 3,4-dihydroxyphenylalanine and 3 parts of sodium bisulfate were weighed and stirred by weight, and then the mixture was kept warm at 75°C for 20 hours under a nitrogen atmosphere, and then cooled to room temperature and the mixture was collected. The mixture was added to acetone at a volume ratio of 1:8, stirred and mixed, and allowed to stand for aging, and the precipitate was filtered and collected. The precipitate was then added to a 5% ferric chloride solution by mass at a mass ratio of 1:10, placed in a beaker, stirred and mixed, and a metal complex sol solution was collected;
[0047] Nano-molybdenum disulfide was added to 1.3 mol / L citric acid solution at a mass ratio of 1:8, and then the mixture was kept at 75°C for 3 hours, and then cooled to room temperature to obtain a matrix gel solution. At room temperature, the metal complex sol solution was added to the matrix gel solution, and then ultrasonically dispersed at 250W for 10 minutes to obtain a modified dispersed gel solution.
[0048] Take the tool and grind it with 800#, 1200# and 1500# sandpaper respectively. After the treatment is completed, rinse it with anhydrous ethanol for 3 times, dry it naturally and collect the surface treated tool;
[0049] The modified dispersed gel liquid is applied to the surface of the surface treated tool, and after drying, it is placed in a 100°C oven for drying for 3 hours, and then heated to 150°C at 3°C / min, and after heat treatment for 3 hours, it is heated to 300°C at 1°C / min, and heat-treated and cooled to room temperature to obtain a surface-coated modified tool;
[0050] Take the surface-coated modified tool and place it on a turntable, place the turntable in a closed coating device, pass nitrogen to exclude air and evacuate to 65Pa, heat to 480℃, keep warm and use Cr as the target, deposit at an arc current of 400A, deposit a 0.05μm CrN bonding layer on the surface-coated modified tool, and then coat it with AlCrN at 480℃ and a pressure of 65 to prepare a composite tool coating.
[0051] Example 2
[0052] Polyvinyl alcohol was added to dimethyl sulfoxide at a mass ratio of 1:25, the mixture was stirred and mixed, and the mixture was collected. The mixture was then added to a three-necked flask, stirred and mixed, and 47 parts of the mixture, 4 parts of 3,4-dihydroxyphenylalanine, and 4 parts of sodium bisulfate were weighed and stirred by weight, and then the mixture was kept warm at 77°C for 22 hours under a nitrogen atmosphere, and then cooled to room temperature and the mixture was collected. The mixture was added to acetone at a volume ratio of 1:8, stirred and mixed, and allowed to stand for aging, and the precipitate was filtered and collected. The precipitate was then added to a 5% ferric chloride solution by mass at a mass ratio of 1:10, placed in a beaker, stirred and mixed, and a metal complex sol solution was collected;
[0053] Nano-molybdenum disulfide was added to 1.3 mol / L citric acid solution at a mass ratio of 1:8, and then the mixture was kept at 80°C for 4 hours, and then cooled to room temperature to obtain a matrix gel solution. At room temperature, the metal complex sol solution was added to the matrix gel solution, and then ultrasonically dispersed at 275W for 12 minutes to obtain a modified dispersed gel solution.
[0054] Take the tool and grind it with 800#, 1200# and 1500# sandpaper respectively. After the treatment is completed, rinse it with anhydrous ethanol for 4 times, dry it naturally and collect the surface-treated tool;
[0055] The modified dispersed gel liquid is applied to the surface of the surface treated tool, and after drying, it is placed in a 105°C oven for 4 hours, and then heated to 165°C at 3°C / min, and after heat treatment for 4 hours, it is heated to 325°C at 1°C / min, and heat-treated and cooled to room temperature to obtain a surface-coated modified tool;
[0056] Take the surface-coated modified tool and place it on a turntable, place the turntable in a closed coating device, pass nitrogen to remove air and evacuate to 72Pa, heat to 525℃, keep warm and use Cr as the target material, and deposit it at an arc current of 450A. Deposit a 0.07μm CrN bonding layer on the surface-coated modified tool, and then perform a secondary deposition at 490℃, pressure of 72Pa, and use AlCr as the target material at an arc current of 450A to form a 4μm AlCrN coating layer, and then prepare a composite tool coating.
[0057] Example 3
[0058] Polyvinyl alcohol was added to dimethyl sulfoxide at a mass ratio of 1:25, the mixture was stirred and mixed, and the mixture was collected. The mixture was then added to a three-necked flask, stirred and mixed, and 50 parts of the mixture, 5 parts of 3,4-dihydroxyphenylalanine, and 5 parts of sodium bisulfate were weighed and stirred by weight, and then the mixture was kept warm at 80°C for 24 hours under a nitrogen atmosphere, and then cooled to room temperature and the mixture was collected. The mixture was added to acetone at a volume ratio of 1:8, stirred and mixed, and allowed to stand for aging, and the precipitate was filtered and collected. The precipitate was then added to a 5% ferric chloride solution by mass at a mass ratio of 1:10, placed in a beaker, stirred and mixed, and a metal complex sol solution was collected;
[0059] Nano-molybdenum disulfide was added to 1.3 mol / L citric acid solution at a mass ratio of 1:8, and then the mixture was kept at 85°C for 5 hours, and then cooled to room temperature to obtain a matrix gel solution. The metal complex sol solution was added to the matrix gel solution at room temperature, and then ultrasonically dispersed at 300W for 15 minutes to obtain a modified dispersed gel solution.
[0060] Take the tool and grind it with 800#, 1200# and 1500# sandpaper respectively. After the treatment is completed, rinse it with anhydrous ethanol for 5 times, dry it naturally and collect the surface-treated tool;
[0061] The modified dispersed gel liquid is applied to the surface of the surface treated tool, and after drying, it is placed in a 110°C oven for drying for 5 hours, and then heated to 180°C at 3°C / min, and after heat treatment for 5 hours, it is heated to 350°C at 1°C / min, and heat-treated and cooled to room temperature to obtain a surface-coated modified tool;
[0062] Take the surface-coated modified tool and place it on a turntable, place the turntable in a closed coating device, pass nitrogen to exclude air and evacuate to 80Pa, heat it to 550℃, keep it warm and use Cr as the target material, and deposit it at an arc current of 500A. Deposit a 0.10μm CrN bonding layer on the surface-coated modified tool, and then perform a secondary deposition treatment of 5μm AlCrN coating layer at 500℃ and a pressure of 80Pa with AlCr as the target material at an arc current of 500A to prepare a composite tool coating.
[0063] Example 4
[0064] In Example 4, zinc chloride solution is used to replace the ferric chloride solution in Example 1, and the other conditions and component ratios are the same as those in Example 1.
[0065] Example 5
[0066] In Example 5, aluminum chloride solution is used to replace the ferric chloride solution in Example 1, and the other conditions and component ratios are the same as those in Example 1.
[0067] Performance testing
[0068] The performance tests were carried out on Examples 1 to 5 respectively, and the coating film-substrate bonding force, coating friction and wear performance, coating microhardness and bonding strength between the coating and the substrate were tested on the tool coatings prepared in Examples 1 to 5.
[0069] Detection method / test method
[0070] (1) Bonding strength: The Rockwell indentation method is used to characterize the bonding strength of the hard coating. The load of the hardness tester is 150 kg and the loading time is 15 seconds. The indentation morphology on the film surface can be used to qualitatively judge the level of its film-based bonding strength. The evaluation standard is the German VDI3198 standard. In this experiment, the indentation method uses the LC-200R Rockwell hardness tester equipment from Japan FT, and then the morphology of the Rockwell indentation is characterized by a high-power scanning electron microscope and Zeiss Smartzoom5 three-dimensional digital microscope. The bonding level HF is determined by the cracks or film loss in the middle or around the indentation combined with the existing standards.
[0071] (2) Coating film-substrate bonding strength: measured using the WS-2005 coating adhesion automatic scratch tester, with a scratch length of 4 mm and a test load of 70 N; measurement method: acoustic signal, friction force; operation mode: dynamic load; scratch method: reciprocating scratch. In each test, the coating film-substrate bonding strength is comprehensively determined by the acoustic emission signal, friction curve and the position of the coating scratch. Each coating is tested four times and the average of the four test results is taken;
[0072] (3) Friction and wear performance of coating: The coating was subjected to dry friction and wear test using HSR-2M reciprocating / rotating friction and wear tester. The friction mode was reciprocating, the sensor specification was 1-10N, and the friction pair was Si3N4 ceramic ball with a diameter of 4mm and a reciprocating length of 5mm. The measured parameters included friction coefficient and friction force. The heating range of the sample heating furnace was from room temperature to 300℃, and the maximum temperature was set to 250℃ during use.
[0073] (4) Microhardness of coating: The microhardness of the coating was measured using a HXD-1000TMD microhardness tester. Test parameters: 136° diamond square pyramid indenter, load 50g, loading time 10s. First, load the test piece according to the test parameters, unload the load after loading, and then measure the length of the diagonal of the test piece under an optical microscope. Finally, calculate the microhardness of the test piece according to the Vickers hardness calculation formula.
[0074] The specific test results are shown in Table 1 below:
[0075] Table 1 Performance test table
[0076]
[0077] By referring to Table 1, we can find that:
[0078] The performance of Examples 1-3 was compared, among which Example 3 had the best performance in terms of comprehensive comparison of microhardness, coating film-substrate bonding force, friction coefficient and bonding strength. At the same time, both the average friction coefficient and microhardness affected the performance of the tool coating. It can also be said that among Examples 1 to 3, Example 3 had the best coating service life and bonding strength with the base layer. This is because the proportion of material added in Example 3 is the highest, which also indirectly reflects that the technical solution of the present application is feasible.
[0079] The performance of Example 1 and Examples 4 to 5 is compared. Since different metal ion solutions are used in Examples 4 to 5, compared with the performance test data in Table 1, the aluminum chloride solution used in Example 5 has the best performance. This is because the technical solution of the present application uses the addition modification of the Al element, and the aluminum chloride solution is used as the raw material for preparation in the interface layer, which can effectively improve the bonding performance between the interface layer and the coating layer, thereby further improving the bonding strength of the interface layer, so that the performance in Example 5 is the best. At the same time, the zinc chloride solution in Example 4 has a higher activity and can effectively improve the bonding strength between the interface layer and the coating and the substrate. Therefore, compared with Example 1, its performance is also higher than that of Example 1.
[0080] Comparative Example
[0081] Comparative Examples 1 to 3
[0082] In Comparative Examples 1-3, the interface layer is not coated on the tool surface but the coating is directly deposited, and the other conditions and component proportions are the same as those in Examples 1-3.
[0083] Comparative Examples 4 to 6
[0084] In Comparative Examples 4-6, the interface layer prepared by adding no metal complex sol solution was coated, and the other conditions and component ratios were the same as those in Examples 1-3.
[0085] Comparative Examples 7 to 9
[0086] In comparative examples 7 to 9, when depositing the AlCrN coating layer, the deposition thickness was controlled to be 2 μm, and the other conditions and component ratios were the same as those in embodiments 1 to 3.
[0087] Comparative Examples 10 to 12
[0088] In Comparative Examples 10-12, when depositing the CrN bonding layer, the thickness of the deposited CrN bonding layer was 0.2 μm, and the other conditions and component ratios were the same as those in Examples 1-3.
[0089] Performance testing
[0090] The tool coatings prepared in Comparative Examples 1 to 12 were tested respectively, specifically the coating film-substrate bonding force, the coating friction and wear performance, the coating microhardness and the bonding strength between the coating and the substrate were tested.
[0091] Detection method / test method
[0092] (1) Bonding strength: For comparative examples 1 to 12, the Rockwell indentation method was used to characterize the bonding strength of the hard coating. The load of the hardness tester was 150 kg and the loading time was 15 s. The indentation morphology on the film surface can be used to qualitatively judge the level of its film-based bonding strength. The evaluation standard is the German VDI3198 standard. In this experiment, the indentation method uses the LC-200R Rockwell hardness tester equipment of Japan FT, and then the morphology of the Rockwell indentation is characterized by a high-power scanning electron microscope and a Zeiss Smartzoom5 three-dimensional digital microscope. The bonding level HF is determined by the cracks or film loss in the middle or around the indentation combined with the existing standards.
[0093] (2) Coating film-substrate bonding strength: measured using the WS-2005 coating adhesion automatic scratch tester, with a scratch length of 4 mm and a test load of 70 N; measurement method: acoustic signal, friction force; operation mode: dynamic load; scratch method: reciprocating scratch. In each test, the coating film-substrate bonding strength is comprehensively determined by the acoustic emission signal, friction curve and the position of the coating scratch. Each coating is tested four times and the average of the four test results is taken;
[0094] (2) Friction and wear performance of coating: The coating was subjected to dry friction and wear test using HSR-2M reciprocating / rotating friction and wear tester. The friction mode was reciprocating, the sensor specification was 1-10N, and the friction pair was Si3N4 ceramic ball with a diameter of 4mm and a reciprocating length of 5mm. The measured parameters included friction coefficient and friction force. The heating range of the sample heating furnace was from room temperature to 300℃, and the maximum temperature was set to 250℃ during use.
[0095] (4) Microhardness of coating: The microhardness of the coating was measured using a HXD-1000TMD microhardness tester. Test parameters: 136° diamond square pyramid indenter, load 50g, loading time 10s. First, load the test piece according to the test parameters, unload the load after loading, and then measure the length of the diagonal of the test piece under an optical microscope. Finally, calculate the microhardness of the test piece according to the Vickers hardness calculation formula.
[0096] The specific test results are shown in Table 2 below:
[0097] Table 2 Performance test table
[0098]
[0099] The performance test table in Table 2 is analyzed as follows:
[0100] Comparing Comparative Examples 1 to 3 of the present application with Examples 1 to 3, the microhardness and bonding performance of the tool hard coating prepared without the interface layer in the comparative examples all showed a significant decrease, which shows that the interface layer used in the present application can significantly improve the bonding strength between the tool surface and the hard coating, so that when the hard coating is subjected to external force, the stress concentration caused by the external force can be unloaded by the high load-bearing performance of molybdenum disulfide, thereby reducing the coating damage phenomenon. The bonding strength between the AlCrN tool coating and the tool surface is effectively improved, and the shedding phenomenon of the AlCrN hard coating is reduced.
[0101] Comparing Comparative Examples 4 to 6 of the present application with Examples 1 to 3, the comparative examples did not use the metal complex sol solution for addition, so that the performance thereof was reduced. Such an interface layer had poor bonding performance with the tool surface, which indicates that the present application can effectively adhere to the surface of the tool material, thereby effectively improving the density performance of the interface layer and improving the shedding phenomenon of the AlCrN hard coating.
[0102] Comparative Examples 7 to 9 of the present application are compared with Examples 1 to 3. In the comparative examples, when depositing the AlCrN coating layer, the deposition thickness is controlled to be 2 μm. Since the thickness of the AlCrN coating layer is reduced, its hardness is significantly reduced during actual use. This shows that optimizing the thickness of AlCrN can effectively improve the strength of the hard coating and make it have excellent hardness performance, so that it can produce good impact resistance against collisions with high hardness materials during use.
[0103] Comparing the comparative examples 10 to 12 of the present application with the embodiments 1 to 3, the thickness of the bonding layer in the comparative examples was increased, resulting in a decrease in material performance. This shows that the optimized bonding layer thickness in the technical solution of the present application effectively reduces the structural effect of the overall coating caused by the excessive thickness of the bonding layer. Therefore, the optimized CrN bonding layer can not only effectively improve the structural performance of the hard coating material, but also effectively reflect its high hardness and low friction coefficient.
[0104] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.
[0105] Although the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the claims and their equivalents.
Claims
1. A composite tool coating, characterized in that: The composite tool coating comprises an interface layer, a CrN bonding layer and an AlCrN coating layer which are sequentially coated from the inside to the outside; The interface layer is prepared by mixing the metal complex sol solution and the matrix gel solution and dispersing them, collecting the modified dispersed gel solution and coating it on the surface of the surface treated tool, heating and calcining after drying, and cooling to room temperature to obtain the interface layer; The matrix gel solution is prepared by mixing nano-molybdenum disulfide and citric acid solution; The preparation steps of the metal complex sol solution are: (1) Add polyvinyl alcohol to dimethyl sulfoxide at a mass ratio of 1:25, stir to mix and collect the mixed solution; (2) taking 45 parts of the mixed solution, 3 parts of the metal complex and 3 parts of sodium bisulfate, stirring and mixing, and heating and keeping warm for reaction treatment under a nitrogen atmosphere to obtain a mixed solution; the metal complex is 3,4-dihydroxyphenylalanine; The temperature of the heat preservation reaction treatment is 75°C and the time is 20h; (3) adding the mixed solution to acetone at a volume ratio of 1:8, stirring and mixing, standing and aging, filtering and collecting the precipitate, and adding the precipitate to a 5% by mass metal ion solution at a mass ratio of 1:10 to obtain a metal complex sol solution; the metal ion solution is a zinc chloride solution or an aluminum chloride solution; The thickness of the CrN bonding layer is 0.05 μm, and the thickness of the AlCrN coating layer is 3 to 5 μm; The preparation method of the composite tool coating comprises: S1, taking a cutting tool, grinding it, washing it, and letting it stand and dry to obtain a surface-treated cutting tool; S2, mixing the metal complex sol solution and the matrix gel solution and dispersing them, collecting the modified dispersed gel solution and applying it to the surface of the surface treated tool, heating and heat preservation after drying, and cooling to room temperature to obtain an interface layer; the heating and heat preservation calcination steps are: heating to 150-180°C at 3°C / min, heat preservation for 3-5h, and then heating to 300-350°C at 1°C / min, and heat preservation; S3, after the interface layer coating is completed, the tool coated with the interface layer is placed on a rotating rack, and Cr is used as a target material to deposit a CrN bonding layer; the CrN bonding layer deposition temperature is 480-550°C; S4. After the CrN bonding layer is deposited, an AlCrN coating layer is deposited using AlCr as a target material to prepare a composite tool coating; the AlCrN coating layer is deposited at a temperature of 480-500°C.
2. A method for preparing a composite tool coating according to claim 1, characterized in that: The preparation method of the composite tool coating comprises: S1, taking a cutting tool, grinding it, washing it, and letting it stand and dry to obtain a surface-treated cutting tool; S2, mixing the metal complex sol solution and the matrix gel solution and dispersing them, collecting the modified dispersed gel solution and applying it to the surface of the surface treated tool, heating and heat preservation after drying, and cooling to room temperature to obtain an interface layer; the heating and heat preservation calcination steps are: heating to 150-180°C at 3°C / min, heat preservation for 3-5h, and then heating to 300-350°C at 1°C / min, and heat preservation; S3, after the interface layer coating is completed, the tool coated with the interface layer is placed on a rotating rack, and Cr is used as a target material to deposit a CrN bonding layer; the CrN bonding layer deposition temperature is 480-550°C; S4. After the CrN bonding layer is deposited, an AlCrN coating layer is deposited using AlCr as a target material to prepare a composite tool coating; the AlCrN coating layer is deposited at a temperature of 480-500°C.
3. The method for preparing a composite tool coating according to claim 2, characterized in that: The grinding process described in step S1 is performed by using 800#, 1200# and 1500# sandpaper respectively.
Citation Information
Patent Citations
Preparation method of soft coating of hard alloy cutter
CN102181849A
Cutter with soft and hard composite coatings
CN102367015A
Corrosion-resistant treatment method for metal welding line
CN108262228A